2020
DOI: 10.1515/cdbme-2020-3121
|View full text |Cite
|
Sign up to set email alerts
|

Printing of vessels for small functional tissues – a preliminary study

Abstract: Vascularization of bioprinted constructs to ensure sufficient nutrient supply still remains to be a significant task in the tissue engineering community. In order to mimic functional tissue, it is necessary to be able to print vessels in various size scales, which places particularly high demands on the 3D printing technology and materials. In this preliminary study, we focused on the production of small hollow structures for the application in small functional units of living tissue. To fabricate hollow struc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 10 publications
0
3
0
Order By: Relevance
“…The in vitro recapitulation is largely achieved by exploiting a variety of bioengineering approaches, including microfluidics [7,66,[70][71][72] and, more recently, 3D printing and bioprinting. [73][74][75][76][77][78][79] These bioengineering approaches play a key role in organizing cells and biomaterials into physiology-relevant structures. For example, microfluidics is based on soft lithography/micromolding and has been widely used to construct vessel analogs, i.e., perfusable microchannels, on a 2D plane [36,80] and 3D interconnected vasculature analogs.…”
Section: Introductionmentioning
confidence: 99%
“…The in vitro recapitulation is largely achieved by exploiting a variety of bioengineering approaches, including microfluidics [7,66,[70][71][72] and, more recently, 3D printing and bioprinting. [73][74][75][76][77][78][79] These bioengineering approaches play a key role in organizing cells and biomaterials into physiology-relevant structures. For example, microfluidics is based on soft lithography/micromolding and has been widely used to construct vessel analogs, i.e., perfusable microchannels, on a 2D plane [36,80] and 3D interconnected vasculature analogs.…”
Section: Introductionmentioning
confidence: 99%
“…Specifically, supporting our hypothesis, our 3D bioprinted patches showed that it is possible for endothelial cells to self-organise into a structural network. Other studies have previously used differing approaches to describe advances in endothelial cell network assembly (Ong et al, 2017b;Cui et al, 2019;Polley et al, 2020;Xu et al, 2020). We have added to this a 3D rendering of micrographic data that shows endothelial cells self-organised into a structural network with a lumen-like space with our method (Supplementary Video 2).…”
Section: Discussionmentioning
confidence: 99%
“…During this post-printing phase, the bioink can promote tissue maturation, with durability in culture being an important characteristic to predict hydrogel disintegration (Bishop et al, 2017;, although the optimal moment to transplant after a period in culture has not previously been confirmed. During this phase, cardiomyocyte contractility should be permitted and endothelial cells within the bioprinted tissue should be permitted to organise into networks, as one of the major challenges in 3D bioprinting of cardiac tissues is the fabrication of a hierarchical vascular system within tissues (Gentile, 2016;Ong et al, 2017b;Polonchuk et al, 2017;Cui et al, 2019;Polley et al, 2020;Xu et al, 2020).…”
Section: Introductionmentioning
confidence: 99%